Quelles conceptions de l’ironie dans les manuels scolaires en collège et lycée ?
The aim of this article is to assess whether the teaching of irony allows students to acquire a certain mastery of ironic processes by knowing not only how to identify them, but also how to interpret them. The examination of fourteen French textbooks, representative of the current teaching in class from 9th to 11th grade, is carried out according to five complementary parameters: the proposed classifications of irony, its defining contents, its forms of expression, the literary texts and the exercises associated with it. A number of pitfalls emerge from this study, such as the emphasis on identification at the expense of interpretation, a lack of stability and continuity in the content exposed and at the notional level, or even a lack of incentive for students to establish links between categorisations, defining contents and forms of expression of irony.